Performance of Inclined Baffle Column for Pectin Continuous Extraction Process from Cocoa Peel (Theobromacacao) - Soemargono (MATEC Web of Conferences, 2016)
Pectin from cocoa peel was successfully prepared by extraction method in the bubble column reactor. The process could be carried out in batch and continuous, with co-current or counter current flow. Bubble pipe reactor with inclined baffle is expected to reduce the problem from gas flow patterns, jagged sloping bulkhead serves as a bubble breaker that could replace mechanical stirrer. In this study the reactor column sloping bulkhead was used as extractor to recover pectin in the cocoa peel by citric acid (1 N) solvent. Cocoa peel paste and citric acid were entered to the top of the column at 1 : 1 rate ratio by streamed using dosing pump. Nitrogen gas as a medium stirrer flowed counter current from the bottom of the column. Once extraction was completed, the liquid then precipitated by acid alcohol. Pectin solids were washed with alcohol (96%). The temperature of extraction process is maintained at 70° C. The residence time in the column material was determined by feed flow rate (cocoa paste and citric acid), and the volume of suspension that remains in the reactor (V). Residence time equation obtained is: t = (7045.86G-0.1275)/L. The yield of yellowish white precipitate reached up to 5.2973% and methoxyl concentration reached 5,21% for 72 minutes. The experiment shows that the continuous extraction process of pectin in baffle columns is better than batch process.